2019
DOI: 10.1177/0956797619885649
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles at Birth Predict Teacher-Rated Child Emotional and Social Development 5 Years Later

Abstract: The fetal environment has been increasingly implicated in later psychological health, but the role of lipids is unknown. Drawing on the ethnically diverse Born in Bradford (BiB) birth cohort, the current study related levels of high-density lipoprotein (HDL), very-low-density lipoprotein (VLDL), and triglycerides in umbilical cord blood to 1,369 children’s teacher-rated psychosocial competence approximately 5 years later. Results of ordinal logistic regressions indicated that low levels of HDL, high levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Furthermore, GO analysis showed that maternal obesity induced methylation changes that were mainly associated with metabolic process and cellular process, which are in accordance with previous study [ 35 ]. This agreement also confirms that newborns from overweight/obese pregnant women were heavier than those from the control group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, GO analysis showed that maternal obesity induced methylation changes that were mainly associated with metabolic process and cellular process, which are in accordance with previous study [ 35 ]. This agreement also confirms that newborns from overweight/obese pregnant women were heavier than those from the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in recent years, it is now known that umbilical cord blood can diagnose the physical and mental health of the fetus. In one of these studies, it was reported that babies with an anomalous lipid level profile at birth may face a higher risk of social and psychological problems in childhood [ 35 ]. Therefore, cord blood testing can be employed to predict the psychological development of children.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated TG levels at birth have been significantly linked with children’s psychological and social functioning 5 years later, suggesting that fetal exposure to lipids may represent a novel form of biological embedding for psychological health risk (Manczak & Gotlib, 2019 ). Moreover, increased levels of TGs with saturated or monounsaturated fatty acyls we observed in our study have been linked with non-alcoholic fatty liver disease (NAFLD) as well as insulin resistance in adults (Oresic et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…141 In addition, longitudinal studies have found that associations of cholesterol levels between birth and adolescence are associated with the later development of depressive symptoms. [142][143][144]…”
Section: N Kappelmann Et Almentioning
confidence: 99%